Interferences in spatial processes in brazilian cities driven by agribusiness: the case of Primavera do Leste (Polis (Santiago), 2019)
Assuming the urban as the guiding perspective of our investigation, we shed light on the production of space in cities whose studies generally emphasize the movements of so-called agribusiness, considered a support for the services and infrastructure required for agriculture. Based on the processes that permeate the city of Primavera do Leste, in the midwest of Brazil, we defend the hypothesis that the concentration of land, power and capital is at the foundation of an urbanization controlled by a small group of people who hold the economic and political power. The interference exercised by the “pioneers” of these cities, characterized today by their agribusiness and established within the so-called expansion of the agricultural frontier starting in the 1970s, goes beyond private property. It reaches a variety of aspects in everyday life and is one of the elements that explains the intensified spatial segregation.
Keywords: Urban; agribusiness; frontier; land concentration; Primavera do Leste.